Remote sensing digital image analysis an introduction - Richards John A; Jia Xiuping (Berlin Springer-Verlag, 2006)
Remote Sensing Digital Image Analysis provides the non-specialist with an introduction to quantitative evaluation of satellite and aircraft derived remotely retrieved data. Each chapter covers the pros and cons of digital remotely sensed data, without de
Keywords: Remote sensing technology